Genome-wide RIP-Chip analysis of translational repressor-bound mRNAs in the Plasmodium gametocyte - Guerreiro, Ana; Deligianni, Elena; Santos, Jorge M.; Silva, Patricia AGC; Louis, Christos; Pain, Arnab; Janse, Chris J.; Franke-Fayard, Blandine; Carret, Celine K.; Siden-Kiamos, Inga; Mair, Gunnar R. (Genome biology, 2014)
Following fertilization, the early proteomes of metazoans are defined by the translation of stored but repressed transcripts; further embryonic development relies on de novo transcription of the zygotic genome. During sexual development of Plasmodium berghei, a rodent model for human malaria species including P. falciparum, the stability of repressed mRNAs requires the translational repressors DOZI and CITH. When these repressors are absent, Plasmodium zygote development and transmission to the mosquito vector is halted, as hundreds of transcripts become destabilized. However, which mRNAs are direct targets of these RNA binding proteins, and thus subject to translational repression, is unknown.